2015
DOI: 10.1111/ecc.12296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sleep disorders in cancer patients based on Pittsburgh Sleep Quality Index

Abstract: Insomnia, poor sleep quality and short sleep durations are the most common problems seen in cancer patients. More studies are needed about sleep disorders in cancer patients. In our study, we aimed to investigate the prevalence of sleep disorders and the impact of these problems on the quality of life in cancer patients. Pittsburgh Sleep Quality Index (PSQI) was given to a total of 314 patients. The psychometric evaluation of the Turkish version of PSQI in cancer patients revealed that 127 (40.4%) patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 44 publications
(76 reference statements)
4
70
2
2
Order By: Relevance
“…We found that the majority of participants with endometrial cancer had global PSQI scores >5 (54.7%), indicating difficulties in overall sleep quality, unlike previous findings (Akman, Yavuzsen, Sevgen, Ellidokuz, & Yilmaz, ; Wu et al., ). Among Turkish people with mixed cancers, only 40% reported poor sleep quality (Akman et al., ). In contrast, 90% of US breast cancer patients with CRF (≥6 of 13 fatigue symptoms) had poor sleep quality (Wu et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the majority of participants with endometrial cancer had global PSQI scores >5 (54.7%), indicating difficulties in overall sleep quality, unlike previous findings (Akman, Yavuzsen, Sevgen, Ellidokuz, & Yilmaz, ; Wu et al., ). Among Turkish people with mixed cancers, only 40% reported poor sleep quality (Akman et al., ). In contrast, 90% of US breast cancer patients with CRF (≥6 of 13 fatigue symptoms) had poor sleep quality (Wu et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…The 19-item Pittsburg Sleep Quality Index (PSQI) assesses sleep quality by asking a series of questions about sleep quality during the past month (Akman, Yavuzsen, Sevgen, Ellidokuz, & Yilmaz, 2015). A global score (ranging 0 to 21) is calculated based on the seven domain scores, with a higher score indicating poorer sleep quality.…”
Section: Methodsmentioning
confidence: 99%
“…yang berdampak langsung pada kondisi fisik dan psikologis pasien, termasuk kualitas tidurnya. Akman et al (2015) telah membuktikan kondisi tersebut dan didapatkan data bahwa kebutuhan istirahat pasien terganggu dan kualitas tidurnya dinyatakan buruk.…”
Section: Pendahuluanunclassified
“…Gangguan tidur sendiri merupakan salah satu masalah fisik yang dialami akibat kanker payudara. Menurut Akman et al (2015), gangguan tidur diketahui memengaruhi kualitas hidup dan psikologis penderita kanker. Gangguan tidur seperti nyeri dapat membangunkan seseorang dari tidur biasanya, mencegah untuk tertidur, dan berkontribusi terhadap hilangnya energi atau kelelahan.…”
Section: Pendahuluanunclassified